The Effects of Changing Sleep Posture on Spinal Symptoms and Quality of Sleep in Cervical and Lumbar Symptomatic Participants - Cary, Doug (Curtin University, 2019)
Patients presenting with waking spinal symptoms to medical services, are a common clinical occurrence, yet treatment is largely based on anecdotal information. A validated measure of sleep posture was developed and used to assess sleep posture in non-symptomatic and symptomatic patients. Differences in sleep routines were noted at baseline and following a sleep posture intervention, sleep posture improved in the symptomatic groups. Further, waking symptoms and sleep quality also improved to 16 weeks follow-up.